Preservation of the symbolic meaning of Ulos in strengthening the cultural identity of the Toba Batak community in Tanjungpinang City - Ranti Miranda Uliarta Manalu; Rafles Hamonangan Simanjuntak; Casiavera Casiavera (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Indonesia has an incredibly diverse culture. This cultural diversity can also realize the representation of culture for the purpose of forming national identity. National identity can use various symbols such as language symbols, traditional dances, and other symbols. Ulos, in this case, is also a symbol used by the Batak community. The research method used in this study is a qualitative method. The results of the study show that: (1) Ulos cannot be separated from the lives of the Batak Toba people because it is an ancestral heritage from ancient times; (2) The symbolic meaning of ulos generally consists of three parts, namely hapal (thick) which provides warmth for the body and soul for those who receive it, sitorop rambu (many signs on the end of ulos) which means to obtain many offspring for those who receive it, and ganjang (long) which means a long life for those who receive it; (3) In every traditional ceremony of the Batak Toba community, the use of ulos is always present because ulos has become an identity for the Batak Toba community. Ulos as an identity for the Batak Toba community can be seen from the type of ulos worn by an individual.